75 years of Tourism Review: survival by transformation: a perspective article. Issue 1 (21st August 2019) - Laesser, Christian; Bieger, Thomas; Pechlaner, Harald; Keller, Peter; Buhalis, Dimitrios
Abstract : Purpose: The purpose of this paper is to reconstruct and analyze the long history of Tourism Review and try to outline the future of this journal. Design/methodology/approach: The authors show that Tourism Review has been a good example of multiple life cycles over time and of survival by adaption. Findings: The authors illustrate also how this journal has seen decline, as well as revival, and stagnation, as well as innovation. Originality/value: It is also a proxy of the state and issues of tourism research and publication over 75 years.